Perbandingan Efektifitas Proses Pembelajaran Menggunakan Metode E-Learning dan Konvensional - Cindy Cahyaning Astuti; Herlinda Maya Kumala Sari; Nuril Lutvi Azizah (International Consortium of Education and Culture Research Studies, 2019)
This study focuses on the comparison between e-learning methods and conventional method (face-to-face) to find out the weaknesses and strengths of e-learning applied at Muhammadiyah University in Sidoarjo. E-Learning used in this study is Edmodo. The research method in this study used Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The sampling technique used is cluster random sampling which is taken proportionally for each cluster. Based on the results of the study it was found that the conventional method (face to face) is still considered better by students than e-learning because it is easier to understand the material and easier to interact with the teacher. However, e-learning itself also has advantages compared to conventional, namely in terms of flexibility in lecture time and ease of collecting assignments